ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE DAN SIZE TERHADAP FIRM VALUE DAN RETURN ON ASSETS PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Maria Lavenia; Werner Ria Murhadi; Arif Herlambang (CALYPTRA, 2018)
This research aims to identify factors that affect the financial performance of a company measured through the approach of market based (firm value) and accounting based (return on assets) such as corporate social responsibility, leverage, and firm size of companies’ listed in the Indonesian Stock Exchange using stakeholders’ theory approaches. This research uses quantitative approach and multiple linear regression method to analyze the data. The target populations of this study are all non-financial companies registered in Indonesia Stock Exchange in 2012-2016 which are equal to 885 year observations. The independent variables used in this study are corporate social responsibility, leverage, and firm size. The study result showed that leverage has a positive significant and firm size has a negative significant impact on firm value. On the other hand, corporate social responsibility has no impact on firm value. Meanwhile, corporate social responsibility, firm size and leverage have negative and significant impact on return on assets.